1995
DOI: 10.1016/0378-1097(95)00127-q
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum 16S rRNA genes

Abstract: The genome of Mycoplasma gallisepticum A5969 contains a truncated pseudogene for 16S rRNA in addition to a single unsplit rRNA-operon and a second discontinuous set of rRNA genes. Other M. gallisepticum strains tested do not possess the truncated gene. This gene is almost identical to full-size isolated 16S rRNA gene starting from at least 500 nucleotides upstream of the coding sequence and ending at the 977th nucleotide within the structural part of 16S rRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…These values may be underestimates because the status of genes of unknown function that have no homologues cannot presently be assessed, but as related genomes are sequenced other instances of damaged currently hypothetical genes may become recognizable (the comparison of two H. pylori isolates has allowed recognition of a few additional apparently damaged genes; Alm et al ., 1999). Truncated gene fragments have been observed even less frequently in bacteria, although a few have been reported especially in association with defective prophages (see, for example, Xiang et al ., 1994; Skamrov et al ., 1995; Casjens, 1998). Smith et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values may be underestimates because the status of genes of unknown function that have no homologues cannot presently be assessed, but as related genomes are sequenced other instances of damaged currently hypothetical genes may become recognizable (the comparison of two H. pylori isolates has allowed recognition of a few additional apparently damaged genes; Alm et al ., 1999). Truncated gene fragments have been observed even less frequently in bacteria, although a few have been reported especially in association with defective prophages (see, for example, Xiang et al ., 1994; Skamrov et al ., 1995; Casjens, 1998). Smith et al .…”
Section: Resultsmentioning
confidence: 99%
“…These values may be underestimates because the status of genes of unknown function that have no homologues cannot presently be assessed, but as related genomes are sequenced other instances of damaged currently hypothetical genes may become recognizable (the comparison of two H. pylori isolates has allowed recognition of a few additional apparently damaged genes; Alm et al, 1999). Truncated gene fragments have been observed even less frequently in bacteria, although a few have been reported especially in association with defective prophages (see, for example, Xiang et al, 1994;Skamrov et al, 1995;Casjens, 1998). Smith et al (1997) have reported a substantial number of damaged genes in the chromosome of Mycobacterium leprae (3.7% pseudogenes in a 1.5 Mbp region), and Andersson et al (1998) observed that 12 of the 846 genes in the complete genome sequence of Rickettsia prowazekii appear to be mutationally damaged and, in addition, ®nd that only 75.4% of its genome appears to encode proteins.…”
Section: Plasmid Rearrangements and Pseudogenes In Othermentioning
confidence: 99%
“…Previously, high genome heterogenity among M. gallisepticum strains and even genome variants of A5969 strain were described [3]. Notably, a truncated gene for 16S rRNA was found only in the A5969 strain [26]. Hence, there is a possibility that fusion of dhfr and dcdA genes in the A5969 strain is a result of a mutation in the intergenic region.…”
Section: Resultsmentioning
confidence: 99%
“…Gene order in rRNA operons and the clusters of ribosomal proteins (especially S10 ribosomal protein region) are well conserved among bacterial species [3–5]. Mycoplasma gallisepticum genome contains two sets of genes for rRNA [6,7]. One set is organized in a ‘classical’ rrn operon ( rrnA , 16S‐23S‐5S).…”
Section: Introductionmentioning
confidence: 99%